Project-Based Learning Improves Process and Outcomes of Grade V Science Learning: Pembelajaran Berbasis Proyek Meningkatkan Proses dan Hasil Pembelajaran Ilmu Pengetahuan Alam Kelas V - Alda, Alda; Sundahry, Sundahry; Agrita, Tri Wera (Indonesian Journal of Innovation Studies, 2025)
General background: Student-centered learning has become an international and national priority, in line with the Sustainable Development Goals (SDGs) and Indonesia’s Kurikulum Merdeka, which emphasize active, contextual, and collaborative learning. Specific background: However, in practice, fifth-grade students at SDN 112 Purwo Bakti demonstrated low engagement and achievement in Ilmu Pengetahuan Alam dan Sosial (IPAS) due to teacher-centered methods. Knowledge gap: While previous studies have applied Project Based Learning (PjBL) in science or social studies separately, limited research addresses its impact on integrated IPAS within the framework of Kurikulum Merdeka. Aims: This study investigates the effectiveness of PjBL in improving both the process and outcomes of IPAS learning in grade V. Results: Through two cycles of classroom action research involving 20 students, teacher performance improved from 80% to 100%, student engagement from 80% to 90%, and learning mastery from 80% to 90%, surpassing the minimum completeness criteria. Novelty: This study uniquely explores the integration of PjBL in IPAS learning as aligned with Kurikulum Merdeka, offering empirical insights rarely examined in primary schools. Implications: Findings highlight that PjBL not only enhances academic achievement but also fosters critical thinking, collaboration, and creativity, providing a sustainable reference for innovative learning strategies in 21st-century education Highlights: PjBL improved student participation and achievement significantly. Integration of PjBL in IPAS is rarely studied at primary level. Supports Kurikulum Merdeka goals for active and contextual learning. Keywords: Project Based Learning, IPAS, Kurikulum Merdeka, Student Engagement, Learning Outcomes